بنية الشخصية في رواية "يسمعون حسيسها" لأيمن العتوم - كير، سناء, عماري، نورة; كرباع، نصيرة (University of El-oued, 2022)
تناول هذا البحث موضوع بنية الشخصية في رواية يسمعون حسيسها للروائي الأردني أيمن العتوم، وانطلاقا من أن لكل رواية شخصيات تحرك السرد فيها فإن هذه الشخصيات بكل أنواعها وأنماطها وكذلك أبعادها رسمت صورة الإنسان بكل ما يحمل من قوى الخير والشر. حيث ربطت بهذه الشخصيات علاقات زمنية ومكانية وأحداث دونت وقائع تاريخ حي في سجن تدمر بسوريا . في الأخير ختم هذا البحث بحوصلة لأهم النتائج المهمة في بناء الشخصية وعلاقتها الإيجابية والسلبية بالمكون السردي في الرواية. This research dealt with the subject of the character structure in a novel they hear its senses the Jordanian novelist Ayman Al-Atoum, and based on the fact that each novel has characters that move the narration in it. These personalities, with all their types and patterns, as well as their dimensions, painted the image of man with all the forces of good and evil. Where she linked to these personalities temporal and spatial relationships and events that recorded the facts of a living history in Palmyra prison in Syria. Finally, this research concludes with a summary of the most important results in character building and its positive and negative relationship with the narrative component of the novel.
Keywords: الشخصية، يسمعون حسيسها، الأبعاد، العلاقة، الزمن، المكان، الحبكة; the character - they hear hissenses - the dimensions - the relationship - the time - the place the plot